In-Stent Stenosis as a Delayed Complication of Neuroform Stent-Supported Coil Embolization of an Incidental Carotid Terminus Aneurysm - Fiorella, David; Albuquerque, Felipe C.; Deshmukh, Vivek R.; McDougall, Cameron G. (American Journal of Neuroradiology, 2004)
Summary: The Neuroform stent is the first microcatheter-delivered stent designed specifically for the treatment of cerebral aneurysms. The stent functions primarily to provide durable parent vessel protection during the embolization of broad-necked cerebral aneurysms. The present case report demonstrates in-stent stenosis occurring as a delayed complication of Neuroform stent-supported coil embolization of an unruptured cerebral aneurysm.